Fundamentals of Delineation of Area of Mineral and hot Water Potential in Duyen Hai area, Hung Ha district, Thai Binh Province, Viet Nam for Exploration Purpose - Hoang, Nguyen Van; Dao, Le Quang; Van, Dong Thu; Hoa, Pham Lan; Hai, Vu Dinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 2, 2020)
Mineral and hot water is a valuable resource that can be used for nursing and physiotherapy, making bottled water, making beverage and healing, exploiting useful minerals, energy extraction, even cultivation spirulina and other purposes. Hot groundwater was discovered during the 90s of the 20th century in Duyen Hai commune, Hung Ha district, Thai Binh province, but no exploration and evaluation studies were conducted to determine the potential of the mineral and hot water in the area. Spatial distribution of groundwater temperature and the total mineralization in the study area of the mineral and hot water occurrence and its surrounding area has allowed to identify the area of mineral and hot water origin, and that the hot water belongs to average hot water with a temperature of about 49 degrees Celsius. Analyzing the tectonic structure has showed that the mineral and hot water is formed at an area surrounded by three class-2 faults, which have a vertical displacement amplitude of 100 m - 1,000 m and a destructive zone of over 100 m. This is an area with favorable conditions to bring geothermal source and dissolved minerals in surrounding rocks to groundwater in the above aquifers. The approach presented in the paper can be applied to conduct research on potential mineral and hot water in other areas: determine values of some mineral and hot water parameters such as temperature and TDS, compile maps of spatial distribution of the parameters, clarify characteristics of tectonic structure relevant to anomaly of high temperature and TDS.